Survivin protein expression is involved in the progression of non-small cell lung cancer in Asians: a meta-analysis. Issue 1 (December 2016) - Duan, Liang; Hu, Xuefei; Jin, Yuxing; Liu, Ruijun; You, Qingjun
Abstract Background Surviving expression might serve as a prognostic biomarker predicting the clinical outcome of non-small cell lung cancer (NSCLC). The study was conducted to explore the potential correlation of survivin protein expression with NSCLC and its clinicopathologic characteristics. Methods PubMed, Medline, Cochrane Library, CNKI and Wanfang database were searched through January 2016 with a set of inclusion and exclusion criteria. Data was extracted from these articles and all statistical analysis was conducted by using Stata 12.0. Results A total of 28 literatures (14 studies in Chinese and 14 studies in English) were enrolled in this meta-analysis, including 3206 NSCLC patients and 816 normal controls. The result of meta-analysis demonstrated a significant difference of survivin positive expression between NSCLC patients and normal controls (RR = 7.16, 95 % CI = 4.63-11.07, P  < 0.001). To investigate the relationship of survivin expression and clinicopathologic characteristics, we performed a meta-analysis in NSCLC patients. Our results indicates survivin expression was associated with histological differentiation, tumor-node-metastasis (TNM) stage and lymph node metastasis (LNM) (RR = 0.80, 95 % CI = 0.73-0.87, P  < 0.001; RR = 0.75, 95 % CI = 0.67-0.84, P  < 0.001; RR = 1.14, 95 % CI = 1.01-1.29, P  = 0.035, respectively), but not pathological type and tumor size. (RR = 1.00, 95 % CI = 0.93-1.07, P  = 0.983; RR = 0.95, 95 % CI = 0.86-1.05, P  = 0.336, respectively). Conclusion Higher expression of survivin in NSCLC patients was found when compared to normal controls. Survivin expression was associated with the clinicopathologic characteristics of NSCLC and may serves as an important biomarker for NSCLC progression.